Public participation: theory and practice in undergraduate occupational therapy training - da Silva, Ana Cristina Cardoso [UNESP]; Oliver, Fátima Correa (FapUNIFESP (SciELO), 2024)
Public participation is part of the debate about transformations and theoretical and methodological diversity in occupational therapy. The aim of this study was to identify whether theoretical and practical aspects of public participation are addressed in undergraduate occupational therapy training and how it has been approached with students. Occupational therapy teachers from public and private universities answered a questionnaire. Most teachers included the concept in theoretical discussions and the development of practices and research inside and outside the classroom. There is a relationship between different fields of work, teaching, research and extension, working methods and methodologies, the population treated and their life contexts, demands and needs, and points of view of public participation. This exemplifies the flexibilization of curriculums and the possibility to chart different pathways for undergraduate training.
Participación social: teoría y práctica en la formación graduada en terapia ocupacional
Participação social: teoria e prática na formação graduada em Terapia Ocupacional
Keywords: Competencies; Occupational therapy; Public participation; Teaching; Teaching-learning methodologies